Correlation analysis of the combined detection of serum CEA, CA72-4, CA19-9 and PGI and postoperative recurrence of gastric cancer: Serum CEA, CA72-4, CA19-9 and PGI in postoperative recurrence of gastric cancer - Han, Bing; Yan, Yuli; Zhong, Yanyan; Li, Xiaoou; Zhang, Yong (Journal of Medical Biochemistry, 2025)
[Objective]: To determine if serum CEA, CA72-4, CA19-9, and PGI in gastric cancer patients following radical gastrectomy are associated with postoperative recurrence. [Methods]: The gastric cancer group consisted of 102 patients who were admitted to our hospital between January 2022 and June 2024 and had undergone radical gastrectomy (RG); the control group consisted of 34 healthy volunteers who were examined during the same time period. Based on whether there was a recurrence following the procedure, patients with gastric cancer were split into two groups: 87 patients who did not experience a recurrence and 15 patients who did. The control group’s serum levels of CEA, CA72-4, CA19-9, and PGI were assessed during physical examination, the day before surgery for gastric cancer patients, and at follow-up (or recurrence) one year later. [Result] In the gastric cancer group, serum levels of PGI were lower than in the control group, whereas CEA, CA72-4, and CA19-9 were greater (all P<0.05). The recurrence rate (15/102 patients) was 14.71%. Poor differentiation degree, decreased PGI, and TNM stage III disease were all independent risk variables for recurrence following RG, according to univariate and multivariate logistic regression analyses (P<0.05). The sensitivity of the serum CEA level was 85.74%, and the specificity was 56.83%. The sensitivity of the serum CA72-4 concentration was 39.46%, and the specificity was 95.13%. Sensitivity of CA19-9 concentration was 58.91%, and the specificity was 78.11%. The AUC of the combined prediction of postoperative recurrence in patients with RG according to CEA, CA72-4, CA19-9 and PGI was greater than that of the individual predictions. [Conclusion]: Patients with RG who had elevated CEA, CA72-4, and CA19-9, decreased PGI, TNM stage III, and little differentiation are at independent risk for postoperative recurrence.